Analysis of Class IV Theme 7 Books Reviewed from the Aspects of Generic Science Skills and Character Values - Restu Windiyarti; Joko Purwanto; Nur Ngazizah (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This analytical research aims to (1) analyze what aspects of generic science skills are contained in class IV thematic books, theme 7, the beauty of diversity in my country, (2) analyze what character values are contained in class IV, theme 7 thematic books, the beauty of diversity in my country . This research uses note-taking technique research. The note-reading technique was carried out to obtain data in the form of material in class IV thematic books, theme 7, the beauty of diversity in my country. This technique is carried out by reading and noting the points of learning material contained in the textbooks on the theme of the beauty of diversity in my country that have been found. Then, the aspects of generic science skills and character values are matched with the material contained in the content standards. Based on the results of the study it can be concluded (1) analysis of aspects of generic science skills contained in class IV thematic books on theme 7 The Beauty of Diversity in My Country there are (50) direct observations, (20) indirect observations, (2) awareness of scales, 15 inferences logic, 5 laws of cause and effect, (1) building new concepts and there are aspects that are not contained in class IV thematic books theme 7 The Beauty of Diversity in My Country there is symbolic language, logical framework, mathematical modeling; (2) analysis of character values contained in the book thematic class IV theme 7 The Beauty of Diversity in My Country there are (9) religious values, (1) honest values, (111) tolerance values, (9) discipline values, (3) hard work values, (37) creative values, (29) independent value, (0) democratic value, (10) curiosity value, (38) national spirit value, (152) love of the motherland value, (14) achievement value, (23) friendly/communicative value, (10) love peace, (3) love to read, (20) value PE caring for the environment, (8) the value of social care, (4) the value of responsibility.